2018
DOI: 10.1039/c7cp06689a
|View full text |Cite
|
Sign up to set email alerts
|

The structures of liquid pyridine and naphthalene: the effects of heteroatoms and core size on aromatic interactions

Abstract: Total neutron scattering has been used in conjunction with H/D and *N/ 15 N isotopic substitution to determine the detailed liquid-state structures of pyridine and naphthalene. Analysis of the data via an empirical potential-based structure refinement method has allowed us to interrogate the full six-dimensional spatial and orientational correlation surfaces in these systems, and thereby to deduce the fundamental effects of a heteroatom and aromatic core-size on intermolecular p-p interactions. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 63 publications
7
44
0
Order By: Relevance
“…9.5 Å, and encompassing approximately 13 neighbour molecules. This scenario is very much resembling the case of naphthalene, a bicyclic aromatic molecule that has been recently explored by joint neutron scattering and Reverse Monte Carlo (EPSR) simulation approaches, where exactly the same coordination shell has been reported, 49 thus suggesting that this organization should not depend upon the aromaticity of the bicyclic compound, but has prevalently steric origin. Driven by these analogies we explored the orientational organization of this first solvation shell, aiming at understanding how a neighbour DBU molecule orients itself around the reference one, as a function of the distance between their CoMs.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…9.5 Å, and encompassing approximately 13 neighbour molecules. This scenario is very much resembling the case of naphthalene, a bicyclic aromatic molecule that has been recently explored by joint neutron scattering and Reverse Monte Carlo (EPSR) simulation approaches, where exactly the same coordination shell has been reported, 49 thus suggesting that this organization should not depend upon the aromaticity of the bicyclic compound, but has prevalently steric origin. Driven by these analogies we explored the orientational organization of this first solvation shell, aiming at understanding how a neighbour DBU molecule orients itself around the reference one, as a function of the distance between their CoMs.…”
mentioning
confidence: 52%
“…This trend is qualitatively identical to the organization reported in Figure 12 of the mentioned paper on liquid structure in naphthalene. 49 The microscopic structural scenario encountered in the protic ionic liquids based on DBU is drastically different from the case of neat DBU. The existence of a net charge on both the anion and the cation introduces coulombic interactions, leading to long-range correlations that have no counterpart in the neutral molecular system; furthermore the possibility of establishing doubly ionic hydrogen bonding 50,51 correlations between cation and anion leads to directional interactions that again have no counterpart in neat DBU.…”
mentioning
confidence: 99%
“…Our previous experiments [15,16], alongside those of Falkowska and co-workers [17,18], have successfully used Neutron Diffraction with Isotopic Substitution (NDIS) interpreted using Empirical Potential Structure Refinement (EPSR) to understand the liquid structure of a number of small aromatics, including benzene, in unprecedented detail. The key feature of the liquid structure of benzene is perpendicular 'Y-stacking' molecules with two hydrogen atoms pointing towards the aromatic ring of the central molecule (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The extension of these force-fields (e.g., OPLS 17 ) to larger aromatic Polyaromatic Hydrocarbons (PAHs) remains relatively untested, save for some preliminary studies. 18 Neutron and X-ray scattering can provide a strong experimental benchmark for solution structure as it can be directly calculated from molecular simulation trajectories from Fourier inversion of the weighted sum of the radial distribution functions in the system 19 . Additionally, molecular simulation is also a valuable tool in analysis of liquid 5 structure from scattering data 20,21 .…”
mentioning
confidence: 99%
“…Results from EPSR can then be used to benchmark force-fields in the ability to predict liquid structure. 21,23 Our recent studies of liquid naphthalene 18 have indicated that standard "aromatic carbon" potentials may not be sufficient to correctly predict liquid structure of polyaromatic hydrocarbons. These EPSR studies of liquid PAHs are a "bottom-up" approach, testing the underlying methods using simple systems.…”
mentioning
confidence: 99%